2019
DOI: 10.1016/j.clnu.2018.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Reduced intestinal FADS1 gene expression and plasma omega-3 fatty acids following Roux-en-Y gastric bypass

Abstract: Roux-en-Y gastric bypass (RYGB) limits food ingestion and may alter the intestinal expression of genes involved in the endogenous synthesis of polyunsaturated fatty acids (PUFAs). These changes may decrease the systemic availability of bioactive PUFAs after RYGB. AIM: To study the impact of RYGB on the dietary ingestion and plasma concentration of PUFAs and on the intestinal expression of genes involved in their endogenous biosynthesis in severely obese women with type 2 diabetes. METHODS: Before, and 3 and 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…These reports, however, do conflict with respect to the changes observed. Our findings match those studies that report an overall decrease in serum or plasma long chain PUFAs following weight-loss surgery [31,48,50]. This is possibly a consequence of reduced dietary intake coupled with increased liberation from adipose stores and increased fatty acid oxidation during significant weight loss [31,49].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These reports, however, do conflict with respect to the changes observed. Our findings match those studies that report an overall decrease in serum or plasma long chain PUFAs following weight-loss surgery [31,48,50]. This is possibly a consequence of reduced dietary intake coupled with increased liberation from adipose stores and increased fatty acid oxidation during significant weight loss [31,49].…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have reported on proportional changes in PUFAs (as opposed to absolute concentrations as reported in the current study) and observed that, although absolute concentrations of these fatty acids decreased, relative proportions were actually increased following metabolic surgery, thus creating a more favourable lipid profile [29,48,51]. In the study by Walle et al, however, subjects were instructed to consume 3 teaspoons of rapeseed oil and 6 tea spoons of mainly rapeseed oil based spreads daily for at least 1e2 years after their weight loss operation and were instructed to consume fish 2e3 times a week.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In our study, FADS1 gene expression was higher in pigs fed the HHD compared to the WD in the jejunal mucosa, and these data were consistent with the estimated D5D enzyme activity in serum. The FADS1 gene encodes for the delta-5 desaturase protein that converts dihomo-gamma-linoleic acid (20:3 n-6, DGLA) to arachidonic acid (20:4 n-6, ARA) and eicosatetraenoic acid (20:4 n-3, ETA) to eicosapentaenoic acid (20:5 n-3, EPA) [ 41 ]. Altered estimated enzyme activity or expression of FADS1 gene has been implied in several disease states, including CAD and insulin resistance [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Under pathophysiological conditions of fat malabsorption, however, micellization of lipophilic compounds might become especially important for supplementation with essential fatty acids. Fat malabsorption occurs due to gastrointestinal diseases, such as Crohn's disease [35], exocrine pancreatic insufficiency [36], cystic fibrosis [37], or after gastric bypass surgery [38]. Similarly, the use of Orlistat, an anti-obesity drug that limits fat absorption by inhibition of pancreatic lipase, leads to fat malabsorption [39].…”
Section: Discussionmentioning
confidence: 99%